2019
DOI: 10.1101/829150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-molecule nanopore sensing of actin dynamics and drug binding

Abstract: Actin is a key protein in the dynamic processes within the eukaryotic cell. To date, methods exploring the molecular state of actin are limited to insights gained from structural approaches, providing a snapshot of protein folding, or methods that require chemical modifications compromising actin monomer thermostability. Nanopore sensing permits label-free investigation of native proteins and is ideally suited to study proteins such as actin that require specialised buffers and cofactors. Using nanopores we de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…3,41 An unfolded protein is typically more surface charged than its folded counterpart due to the exposure of charged moieties that are otherwise hidden due to folding. 42 According to the Hofmeister series, Li + is a chaotropic cation while K + is a kosmotropic cation. 43 It is possible that with voltage-driven unfolding, the ions of the electrolyte would have more access to the otherwise shielded moieties due to the folded structure with chaotropic cations denaturing and destabilizing the protein structure compared to kosmotropic cations.…”
Section: Resultsmentioning
confidence: 99%
“…3,41 An unfolded protein is typically more surface charged than its folded counterpart due to the exposure of charged moieties that are otherwise hidden due to folding. 42 According to the Hofmeister series, Li + is a chaotropic cation while K + is a kosmotropic cation. 43 It is possible that with voltage-driven unfolding, the ions of the electrolyte would have more access to the otherwise shielded moieties due to the folded structure with chaotropic cations denaturing and destabilizing the protein structure compared to kosmotropic cations.…”
Section: Resultsmentioning
confidence: 99%
“…All the nanopipettes were fabricated by pulling quartz capillaries (GQF100-50-7.5, World Precision Instruments, UK) using a laser-assisted pipette puller (Sutter Instrument, P-2000, USA) as per protocol reported previously by our group 33 , 62 . Prior to pulling, the capillaries (inner diameter: 0.5 mm, outer diameter: 1.0 mm, length: 7.5 cm) were cleaned thoroughly for approximately 30 min using a plasma cleaner (Harrick Plasma) to remove any organic residues or contaminants on the quartz surface.…”
Section: Methodsmentioning
confidence: 99%
“… 45 The formation of amyloid fibrils and other filamentous proteins has been studied with nanopores, but complex surface modifications of the nanopore are often required. 46 49 Having demonstrated that macromolecular crowding improves the nanopore sensitivity for globular proteins, we then investigated whether the detection of α-synuclein amyloid fibrils could also be enhanced and whether the length of the amyloid fibrils affected the translocation dynamics. In order to analyze fibrils with distinct length distributions, fragmented and elongated α-synuclein amyloid fibrils were generated (see the Methods in the Supporting Information ).…”
mentioning
confidence: 99%